A Pengaruh Kecerdasan Linguistik Siswa SMA Terhadap Kemampuan Pemecahan Soal Cerita Pada Materi Statistika - Faziana, Muhamad Alung; Hardiani, Nur Hardiani (Jurnal of Math Tadris, 2025)
This study aims to determine the effect of thelinguistic intelligence of 10th grade high school students on their ability to solve story problems in statistics material. This study uses a descriptive qualitative approach. This study uses a simple linear regression design. The sampling technique used in this study was simple random sampling. The data collection method used in this study was a mathematical linguistic intelligence questionnaire consisting of 12 statement items and a descriptive test consisting of 1 item representing the indicator of story problem solving ability. The data analysis techniques used were normality test, linearity test, heteroscedasticity test, and t-test in simple linear regression analysis. The results obtained are the regression equation y ̂ = -10.998 + 2.142x The regression coefficient for variable X is 2.142, which means that if mathematical linguistic intelligence increases by 1%, then the ability to solve mathematical story problems of students (Y) will increase by 2.142 units. And the value of = 0.98 which has a strong influence.